Analisis Crowding Out Effect dan Public Choice dalam Penentuan Anggaran Pendidikan Pemerintah Daerah Studi Kasus 337 Kab./Kota Periode 2001-2005 di Indonesia - Fithria U. M., Irfani (Jurnal Ekonomi dan Pembangunan Indonesia, 2009)
The focus of this study is crowding out effect and public choice mechanism in determination of education expenditures of local government. Education spending has risen significantly over three last decades. Indonesia 2001's decentralization is rapidly moving the country from one of the most centralized system in the world to one of the most decentralized. The country has embarked on a program of fiscal, administrative and political decentralization at the same time. It has been asserted that larger education expenditures have caused local governments to spend less on other types of government services. Using panel of districts-level data for the period of 2001-2005, this study provides a test of the hypothesis that education spending has crowded out other types of spending and tries to find out which party in Indonesia that have preference in education. The results indicate that,for the period studied, there is evidence that increased local government education expenditures resulted in lower levels of speding on other categories of local government provided good and services. Only four parties that pro education are Golkar,Partai Keadilan,Partai Persatuan Pembangunan(PPP) and Partai Kebangkitan Bangsa (PKB). Other results showed that districts located in Java spend higher education expenditures than out of Java and districts with natural resource revenue shares have higher education expenditures as well.